Thermoelectric amplification of phonons in graphene - Dompreh, K.A.; Mensah, N.G.; Mensah, S.Y.; Fosuhene, S.K. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
Amplification of acoustic in-plane phonons due to an external temperature gradient (∇T) in single-layer graphene (SLG) was studied theoretically. The threshold temperature gradient (∇T)0g and the threshold voltage (VT)0g in SLG were evaluated. For T = 77 K, the calculated value for (∇T)0g 746.8 K/cm and (VT)0g=6.6mV. The calculationwas done in the hypersound regime. Further, the dependence of the normalized amplification (Γ/Γ0) on the frequency ωq and ∇T/T were evaluated numerically and presented graphically. The calculated threshold temperature gradient (∇T)0g for SLG was higher than that obtained for homogeneous semiconductors (n-InSb)(∇T)0hom ≈103 K/cm, superlattices (∇T)0SL = 384 K/cm, and cylindrical quantum wire (∇T)0cqw≈102 K/cm. This makes SLG a much better material for thermoelectric phonon amplification.